2000
DOI: 10.1093/clinchem/46.10.1588
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Capacity of Indole Markers in the Diagnosis of Carcinoid Tumors

Abstract: Background: We evaluated the discriminating capacity of the indole markers urinary 5-hydroxyindoleacetic acid (5-HIAA), urinary serotonin, and platelet serotonin in the diagnosis of carcinoid tumors. Methods: Indole markers were measured in 688 patients with suspected carcinoid disease. The initial values of indole markers from patients in whom a carcinoid tumor was confirmed during follow-up (n = 98) were used for ROC analysis. Two groups served as reference populations. The first consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 28 publications
1
53
1
4
Order By: Relevance
“…In a later study, the same group reported that patients with midgut carcinoid tumors had median platelet 5‐HT levels of 23.8 (nmol/10 9 platelets) as compared to 3.4 in normal controls (7.0‐fold increase) 70 . A similar 8.6‐fold increase in platelet 5‐HT was reported by others 71 . Robiolio et al 67 reported that patients with carcinoid syndrome and VHD had higher serum and platelet 5‐HT levels than carcinoid patients without VHD.…”
Section: Discussionsupporting
confidence: 60%
“…In a later study, the same group reported that patients with midgut carcinoid tumors had median platelet 5‐HT levels of 23.8 (nmol/10 9 platelets) as compared to 3.4 in normal controls (7.0‐fold increase) 70 . A similar 8.6‐fold increase in platelet 5‐HT was reported by others 71 . Robiolio et al 67 reported that patients with carcinoid syndrome and VHD had higher serum and platelet 5‐HT levels than carcinoid patients without VHD.…”
Section: Discussionsupporting
confidence: 60%
“…Darüber hinaus werden für das Karzinoid-Syndrom neben Serotonin auch die Sekretion weiterer Tachykinine wie Substanz P und Neurokinin A verantwortlich gemacht, sodass in seltenen Fällen die 5-HIES-Ausscheidung auch beim Vorhandensein eines Karzinoid-Syndroms unauffällig sein kann, insbesondere wenn keine Durchfälle bestehen [68]. Durch Absenken des Grenzwerts auf 2,8 mmol/mol Kreatinin kann die Sensitivität auf 68 % angehoben werden (bei 89 % Spezifität), während bei einem hohen Grenzwert von 6,7 mmol/mol Kreatinin die Sensitivität bei nur 52 % liegt, aber die Spezifität bei 98 % [70]. Es besteht keine gute Korrelation zwischen der Höhe der 5-HIES-Spiegel und dem Schweregrad der Symptome, was wahrscheinlich auf eine fluktuierende Serotoninsekretion durch den Tumor und zusätzliche Mediatoren des Karzinoid-Syndroms zurückzuführen ist.…”
Section: Starke Empfehlung Konsensunclassified
“…Sometimes serotonin‐secreting PNETs are classified with use of tissue samples (serotonin staining); however, this does not always reflect clinical functionality of the tumour as assessed by determining the 24‐hours urinary 5‐hydroxyindoleacetic acid (5‐HIAA) excretion . In gastrointestinal NETs, 24‐hours urinary 5‐HIAA excretion has a high sensitivity and specificity for detecting metastatic midgut NETs, but it is less useful for predicting survival during follow‐up . In PNETs, the incidence and the effect of elevated 24‐hours urinary 5‐HIAA excretion on survival is unknown.…”
Section: Introductionmentioning
confidence: 99%